The Influence of Financial Knowledge, Attitudes to Finance, and Lifestyle on Interest in Online Loans in Bengkalis Regency Accounting Students - Siti Aisah; Rosmida Rosmida (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of financial knowledge, financial attitudes, and lifestyle on the use of online loans in accounting students in Bengkalis Regency. The background of this research began with the increasing use of online loan services among students who were influenced by ease of access, fast processes, and attractive promotions. This phenomenon raises concerns because some students still have low financial literacy and a high consumptive lifestyle. The research uses a quantitative approach by distributing questionnaires to students of the accounting study program who are actively using online loan services. The data analysis technique uses Partial Least Square (PLS) to evaluate the relationship between variables. The results of the study show that financial knowledge has a positive but not significant effect on online loan interest. Financial attitudes have a positive and significant effect on interest in online loans, while lifestyle also has a positive and significant influence. These findings show that students' decisions to use online loans are more influenced by attitudes and lifestyles than financial knowledge levels. This research is expected to contribute to understanding student financial behavior and become an input for educational institutions in improving the financial literacy of the younger generation.